Spontaneous Norms in Law and Economics: A Sketch Typology - Karol B. Zdybel (University of Hamburg, Institute of Law and Economics (ILE), 2023)
This article offers a concise typology of spontaneous norms - i.e., norms that are formed or sustained through decentralized collective behavior in a community. The typology combines three criteria for identifying spontaneous norms: (i) implicit formation of (customary) rules, as opposed to explicit formation; (ii) enforcement through decentralized sanctioning actions, as opposed to enforcement by a special social agent; (iii) private interpretation of compliance with rules, as opposed to the presence of a public interpreter of compliance. The paper also suggests how identified types can be modeled game-theoretically as repeated games. It is argued that structural differences between various types of spontaneous norms can be best understood as differences in the sequence of play in a stage game. Further, the typology is illustrated with examples from legal history and legal anthropology. Supposedly dissimilar systems of norms (e.g., customary international law and primitive law; norms of warfare and domestic social norms) are shown to exhibit structural resemblance.
Keywords: B41; K00; N40; O17; 330; spontaneous norms; custom; customary law; social norms; comparative legal history; typology